Computational anatomical animal models : methodological developments and research applications - Zaidi, Habib (IOP (Series). Release 6., 2018)
Computational Anatomical Animal Models: Methodological developments and research applications provides a comprehensive review of the history and technologies used for the development of computational small animal models with a focus on their application in preclinical imaging and experimental radiation therapy, as well as non-ionizing and ionizing radiation dosimetry calculations. It also provides an overview of the overall process involved in the design of these models, including the fundamental elements used for the construction of different types of computational models, the identification of original anatomical data, the simulation tools used for solving various computational problems and the applications of computational animal models in preclinical research. Part of IPEM-IOP Series in Physics and Engineering in Medicine and Biology.